Postethnophilosophy - Osha, Sanya. (Value Inquiry Book Series, 2011)
This book makes a bold announcement for the beginning of a postethnophilosophical phase in modern African thought. It re-considers the question: "What is African philosophy," and introduces a strategy for setting a broad and productive agenda for contemporary African philosophical thought.